2003
DOI: 10.1038/sj.ejcn.1601742
|View full text |Cite
|
Sign up to set email alerts
|

Daily moderate amounts of red wine or alcohol have no effect on the immune system of healthy men

Abstract: Objective: To investigate whether the daily intake of red wine (RW) at a dose which inversely correlates with cardiovascular disease (CVD) risk modulates immune functions in healthy men. Design: Randomized single-blind trial with four intervention periods. Setting: The Institute of Nutritional Physiology, Federal Research Centre for Nutrition, Karlsruhe, Germany. Subjects: A total of 24 healthy males with moderate alcohol consumption patterns were recruited and all completed the study. Intervention: Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 40 publications
(47 reference statements)
3
21
1
Order By: Relevance
“…A study with similar design assessing the same immune parameters was run immediately after the present carotenoid study. Compared to baseline, no significant changes for control and treatment group during a 12-week period were found [29]. This argues against the idea that the changes in immune functions measured in our study were a chance finding and not related to carotenoid depletion and juice supplementation.…”
Section: Discussioncontrasting
confidence: 54%
“…A study with similar design assessing the same immune parameters was run immediately after the present carotenoid study. Compared to baseline, no significant changes for control and treatment group during a 12-week period were found [29]. This argues against the idea that the changes in immune functions measured in our study were a chance finding and not related to carotenoid depletion and juice supplementation.…”
Section: Discussioncontrasting
confidence: 54%
“…Daily consumption, less than four weeks (-) 500 mL red wine (or alcohol, dealcoholized red wine, or grape juice) for 2 weeks did not affect biomarkers of immune status Watzl et al 2004 Daily consumption, four weeks or more (-) 200 mL red wine (or dealcoholized red wine) for 6 weeks did not modulate immunological functions of leukocytes Ellinger et al 2008 (-/+) 150 mL red wine for 3 weeks slightly reduced fibrinogen levels but did not reduce CRP levels Retterstol et al 2005 (+) 20 g ethanol (220 mL b ) red or white wine by females for 4 weeks caused a down-regulation of adhesion molecules and other inflammatory biomarkers; red wine was more effective than white wine Sacanella et al 2007 (+) Greater than 14 drinks red wine per week (~300 mL daily b ) (but not consumption of other alcoholic beverages) was associated with a decreased risk of common cold Takkouche et al 2002 (+) 30 g alcohol (330 mL b ) red wine or gin for 1 month showed anti-inflammatory effects Estruch et al 2004 disease. Endothelial cells play a major role in regulating the balance between the synthesis and interaction of proteins that promote clot formation and fibrinolytic proteins that facilitate fibrinolysis (clot lysis).…”
Section: Dose/effect a Finding Referencementioning
confidence: 99%
“…Watzl et al showed that both acute (53) and chronic (54) administration of red wine, de-alcoholized red wine and red grape juice had no effect on cytokine production, phagocytic activity of neutrophils and monocytes, lymphocyte proliferation and lytic activity of natural killer cells. However, Estruch et al (55) found reduced plasma levels of fibrinogen, IL-1a, CRP, vascular cell adhesion molecule-1 and intercellular adhesion molecule-1 and an increase in plasma levels of epigallocatechin, after 4 weeks of red wine consumption.…”
Section: Anti-inflammatory Properties Of Flavonoidsmentioning
confidence: 99%